Effectiveness of Progressive Muscle Relaxation as Complementary Therapy in Managing Blood Pressure Among Adult with Hypertension - Ady Irawan AM; Reezal bin Ishak; Anggie Pradana Putri; Totok Wahyudi; Ikrima Rahmasari (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Hypertension is a major cause of premature death worldwide. Some complementary health approaches are showing promise to lowering blood pressure, one of which is progressive muscle relaxation (PMR). This study aimed to determine the effectiveness od progressive muscle relaxation as complementary therapy in managing blood pressure among adult with hypertension. This was a quasi-experimental design with pre and post-test with control group approach. Stratified random sampling was done to determine the research area, followed by purposive sampling to recruit the respondents. Sample size was calculated using G-Power analysis. There were 62 respondents for intervention group and 60 respondents for control group. After 12 sessions of PMR in six days, there was a decreased systolic blood pressure to 29.9 mmHg and diastolic blood pressure to 14.7mmHg. PMR significantly decreased systolic and diastolic blood pressure among adult with hypertension. PMR as complementary therapy could be combined with pharmacological therapy to help ensure a maximum decrease in blood pressure